2020
DOI: 10.2744/ccb-1395.1
|View full text |Cite
|
Sign up to set email alerts
|

Leatherback Sea Turtle (Dermochelys coriacea) Embryo and Hatchling Pathology in Grenada, with Comparison to St. Kitts

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Many (40%) individuals with pneumonia spent <72 h in rehabilitation, consistent with the view that respiratory infections may be acquired in egg or in nest (Al-Bahry et al 2009; Hill et al 2019). Pneumonia was grossly evident as reddened lungs or lung nodules in a minority of cases, and most cases consisted of bronchopneumonia suggestive of inhaled route of infection, as seen with leatherback, green, and loggerhead hatchlings (Glazebrook et al 1993; Miller et al 2009; Hill et al 2019; Choi et al 2020), but in contrast to the interstitial pneumonia reported in loggerhead hatchlings (Orós et al 2020). However, there were several with an embolic pattern of pneumonia or infectious lesions in other organs, consistent with a hematogenous route of pulmonary infection; few with intralesional foreign material consistent with aspiration; and many with intralesional cocci, fungal hyphae, or mixed microbial agents suggesting more diverse etiology than the gram-negative bacilli described in leatherback hatchling pneumonia (Choi et al 2020).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Many (40%) individuals with pneumonia spent <72 h in rehabilitation, consistent with the view that respiratory infections may be acquired in egg or in nest (Al-Bahry et al 2009; Hill et al 2019). Pneumonia was grossly evident as reddened lungs or lung nodules in a minority of cases, and most cases consisted of bronchopneumonia suggestive of inhaled route of infection, as seen with leatherback, green, and loggerhead hatchlings (Glazebrook et al 1993; Miller et al 2009; Hill et al 2019; Choi et al 2020), but in contrast to the interstitial pneumonia reported in loggerhead hatchlings (Orós et al 2020). However, there were several with an embolic pattern of pneumonia or infectious lesions in other organs, consistent with a hematogenous route of pulmonary infection; few with intralesional foreign material consistent with aspiration; and many with intralesional cocci, fungal hyphae, or mixed microbial agents suggesting more diverse etiology than the gram-negative bacilli described in leatherback hatchling pneumonia (Choi et al 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Preventative measures for this lesion undertaken by the SKSTMN include cleaning externalized yolk sacs when hatchlings are admitted to rehabilitation. Skeletal muscle necrosis, which affected 12% of hawksbills dying during rehabilitation, is common among Caribbean leatherback hatchlings (Miller et al 2009; Hill et al 2019; Choi et al 2020), and has been observed in net-entangled juvenile green and loggerhead sea turtles (Orós et al 2005; Phillips et al 2015). In our study, this lesion was associated with weakness, although weakness was common regardless of underlying disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arhinia is the absence of nares, and it has been reported in the green turtle [ 13 ]. A leatherback sea turtle embryo with holoprosencephaly, arhinia, proboscis, and maxillary micrognathia has been reported, and according to the authors, these malformations could be related to the nutritional status of the mother and/or exposure to mercury [ 53 ]. Agnathia ( Figure 1 ) is the absence of jaws (maxilla and/or mandible); it has been identified (although in low proportions) in green, hawksbill, and olive ridley sea turtle embryos [ 13 , 19 ], and it is closely linked to holoprosencephaly [ 54 ].…”
Section: Craniofacial Disordersmentioning
confidence: 99%
“…Rinoschisis, a peculiar and rare malformation, characterized by vertical separation of the nares into two equal parts, has been identified in hawksbill turtle embryos [ 13 ]; in humans, mutations in the FREM1 gene (FRAS1-related extracellular matrix protein 1) have been reported to cause this malformation [ 95 ]. Another rare malformation is rhinocephaly, consisting of one proboscis-shaped nare generally in the front of the head; it has been reported for olive ridley and leatherback turtle embryos [ 13 , 53 ] related to holoprosencephaly.…”
Section: Craniofacial Disordersmentioning
confidence: 99%